PENINGKATAN PENGETAHUAN DAN SIKAP SISWA SMK N 2 KOTA JAMBI DALAM KESELAMATAN BERKENDARA (SAFETY RIDING) - Rd. Halim; Muhammad Syukri (Jurnal Salam Sehat Masyarakat (JSSM), 2020)
Motor vehicle accidents are multifactorial (human factors, vehicles, and the physical environment).The high percentage of young riders in motorcycle accidents is a serious public health problem. The purpose of this counseling activity is to increase knowledge and attitudes in safety riding. The target of this service activity was 21 students of SMK N 2 Jambi City who were selected purposively. Students are given understanding related to safety riding and then followed by a discussion. Before being given the material, students are asked to fill out a pre-test form to measure knowledge and attitudes, then another measurement was taken after the discussion session in the form of a post-test to find out differences in attitude knowledge before and after counseling. Data analysis used the Wilcoxon test and paired sample t-test. The analysis showed that there were differences in knowledge (p-value = 0.005) and attitudes (p-value = 0.001) before and after counseling. Counseling that has a positive impact so that there is an increase in the knowledge and attitudes of students of SMKN 2 Jambi City.